Manajemen Bandwidth Menggunakan Queue Tree Untuk Aplikasi Youtube - Rizka Dwi Saputri; Rahyul Amri; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Youtube is an application for sharing videos that users can access for free. In the results of a survey that has been carrying out for many users who use Youtube, they experience buffering due to the slow internet network. Therefore, bandwidth management is needed that aims to manage and control customer bandwidth so that bandwidth usage can be evenly distributed by using the Queue Tree Method on Mikrotik. The Queue Tree method is a method that can divide bandwidth by marking the service from the package used by the customer. This research was conducted for five days by comparing the existing conditions and conditions using the Queue Tree Method based on testing one of the Quality Of Service (QoS) parameters such as Delay. The results of the study concluded that the analysis carried out on the QoS Parameters for the Youtube in Existing Conditions obtained a considerable Delay value in the Afternoon time of 524,87 ms, including the Bad Category and the Delay value obtained in Queue Tree Conditions of 11,83 ms included in the Very Good Category. In this case, using the Queue Tree Method, the network quality is better than the existing network conditions because of the bandwidth usage that is distributed evenly to each customer.Keywords: Youtube, Bandwidth Management, Queue Tree, Quality of Service.